Pentahelix collaboration strategy in building city branding of Pangkalpinang as a creative city - Fauzi, Dani; Kurniawan, Kunkun (Jurnal Pariwisata Pesona, 2025)
Some cities have successfully developed effective branding strategies, such as emphasizing creativity in Poland, creativity and modernity in Bandung, Indonesia, and halal tourism in Padang City. Pangkalpinang City currently lacks a clear tourism-focused city branding strategy, which limits its ability to effectively communicate its unique potential This research examines the potential of Pangkalpinang City as a creative destination by addressing its challenges in branding and stakeholder collaboration. The study employs an explanatory sequential mixed-methods approach, integrating quantitative data from 100 respondents with qualitative insights from five key stakeholders. Quantitative findings reveal that while Pangkalpinang excels in accessibility and cultural richness, it struggles with weak tourist engagement and low brand loyalty. Qualitative interviews highlight the need for stronger synergy among academics, government, business, media, and communities using the Pentahelix model. The research concludes that implementing the “Authentic Pangkalpinang” branding strategy—leveraging Malay culture and tin mining heritage—can enhance the city’s identity, foster unique tourist experiences, and encourage sustainable growth. The findings underscore the strategic role of cross-sector collaboration in strengthening Pangkalpinang’s competitiveness as a creative city.